NEW DATA ABOUT THE AGE OF LOWER-MIDDLE DEVONIAN ROCK MASSES IN THE NORTHERN PART OF THE KARASOR SYNCLINORIUM (CENTRAL KAZAKHSTAN) - Belayev O.Ye.; Sorokoletov M.V.; Shchegoleva L.A.; Yurina A.L. (My University, 1996)
The paper present descriptions of the sections of the Saumalkol' Formation situated in the Northern part of the Karasor synclinorium in Central Kazakhstan. Particular attention was devoted to finds of fauna and flora and a microscopic study of the volcanogenic and volcanogenic-sedimentary rocks forming the formation. The data made it possible to recognise a lower sub-formation of Early Emsian age, an upper sub-formation of Late Emsian age and a third sub-formation of Eifelian age, which is considered to constitute a separate formation and is named the Krykoshak Formation.
Keywords: Devonian; Paleozoic::Devonian; Палеозой::Девонская